Due diligence in China : beyond the checklists - Yong, Kwek Ping (J. Wiley & Sons Singapore, 2013)
A plain-English guide that demystifies the business landscape in China from a due diligence point of view Due diligence is crucial to any business deal, and, thankfully, due diligence research has come a long way over the years. What used to be a cumbersome, time-consuming process has been standardized and systemized with generally accepted auditing frameworks and tools, such as the all-important auditing ""checklists."" But when it comes to doing due diligence in China, with its opaque regulatory system and byzantine accounting standards, all bets are off. In this book an acknowledge